The The COVID-19 vaccine during pregnancy phase: A literature review - Vinsensius Tommy Wijaya Jopala; Willam Alexander Setiawan (Indonesian Journal of Perinatology, 2022)
Physiological change makes pregnant women more vulnerable to COVID-19 infection. It raises morbidity and mortality rates in pregnant women in comparison to the general population. Several morbidities have been reported such as earlier miscarriage, vaginal bleeding during pregnancy, edema in all extremities and also the face, hypertension during the gestational phase, foul-smelling vaginal discharge, and dysuria due to urinary tract infection, etc, with the effectiveness, of reducing morbidity and mortality, vaccines play a key role, especially for this group. However, concerns arise about the safe pregnancy and the fetus This paper addressed the most recent knowledge of the COVID-19 vaccine in pregnancy, as well as the vaccine's pathophysiology. and the current study about safeness. Keywords: Covid-19 vaccine, pregnancy, review, safeness of vaccine